E-readiness Evaluation and Training Needs Assessment among Goat Bank Pashusakhis in Maharashtra - Patil, A P; Chander, Mahesh; Verma, M R; Kumar, Sanjay; Kumari, Maina; Johnson, Demian C (Indian Journal of Extension Education, 2024)
ICTs and e-readiness assessments guide organisations in maximizing their digital potential, ensuring a competitive edge in a dynamic economy. In line with this, a study was carried out in 2023 to assess the e-readiness index of Pashusakhis (Livestock para-extension professionals) working for the goat bank in five districts of Maharashtra. Pashusakhis serve as intermediaries between beneficiaries and the goat bank. Six out of 15 ICT-related indicators influencing e-readiness were selected, applying the Principal Component Analysis (PCA) based on rank scores. The analysis revealed a calculated index of 0.34, indicating a relatively lower level of e-readiness among Pashusakhis. Logistic regression identified three determinants, including experience, innovativeness, and economic motivation; which significantly influenced the Pashusakhis’ e-readiness. Additionally, the study identified the training requirements of Pashusakhis based on the significance they attributed to job related areas. Credit and marketing management, kid management, and digital literacy emerged as the most important areas requiring training. These findings highlighted the importance of targeted training in areas such as credit and marketing management, and digital literacy to enhance the e-readiness of Pashusakhis to improve their efficiency as intermediaries in the goat bank ecosystem.
Keywords: Determinants of e-readiness; Digital potential; E-readiness index; Pashusakhi; Training need